A Comparative Study of the Effects of Augmented Reality Application on Movement Accuracy and Subjective Satisfaction in Rehabilitation Training for Individuals with Lower Limb Amputations - Yunhee Chang; Jungsun Kang; Hyeonseok Cho; Sehoon Park (Applied Sciences)
This study investigated the efficacy of Augmented Reality (AR) in the rehabilitation of lower limb amputees by comparing movement accuracy and subjective satisfaction with and without AR. Ten individuals with unilateral lower limb amputations participated. Joint range of motion during exercises was measured using a 3D motion capture system. Subjective satisfaction was assessed via a 5-point Likert scale. Movement accuracy was evaluated by analyzing changes and variability (standard deviation) in joint angles across eight selected movements. Results showed that AR feedback significantly increased average joint angles in specific movements: standing arm raise to the side, standing trunk lateral flexion, and standing knee flexion to maximum height. Furthermore, AR feedback led to a significant reduction in the standard deviation of joint angles for most exercises, indicating improved movement consistency. Subjective satisfaction scores for interest, motivation, exercise effectiveness, movement accuracy, and overall satisfaction were significantly higher with AR.